Widespread changes in sexual behaviour in eastern and southern Africa: Challenges to achieving global HIV targets? Longitudinal analyses of nationally representative surveys. Issue 6 (21st June 2019) - Schaefer, Robin; Gregson, Simon; Benedikt, Clemens
Abstract: Introduction: Sexual behaviour change contributed to reductions in HIV incidence in eastern and southern Africa between 1990 and 2010. More recently, there are indications that non‐regular partnerships have increased. However, the effect of these increases on population‐level risks for HIV and other sexually transmitted infections could have been reduced by simultaneous increases in condom use. We describe recent trends in sexual behaviour and condom use within the region and assess their combined effects on population levels of sexual risk. Methods: Nationally representative Demographic and Health Survey data on sexually active males and females (15 to 49 years) were used for 11 eastern and southern African countries (≥3 surveys for each country; 1999 to 2016) to describe trends in sexual behaviour (multiple, non‐regular, and casual sexual partnerships; condom use; age at first sex). Logistic regressions tested for statistical significance of changes. Analyses were stratified by sex. Results: Recent increases in multiple, non‐regular, and/or casual partnerships can be found for males in 10 countries and, for females, in nine countries; five countries exhibited recent decreases in age of sexual debut. Reduction in sex without condoms with non‐regular partners was observed in six countries for males and eight for females. Changes in the proportion of the overall population reporting condomless sex with non‐regular partners varied between countries, with declines in six countries and increases in three. Conclusions: Extensive change in sexual behaviour occurred across eastern and southern Africa during the period of scale‐up of antiretroviral therapy programmes. This includes increasing multiple and non‐regular partnerships, but their potential effects on population‐level sexual risks were often offset by parallel increases in condom use. Strengthening condom programmes and reintegrating communication about behavioural dimensions into combination prevention programmes could help countries to meet international targets for reductions in HIV incidence.